Effector Memory–Expressing CD45RA (TEMRA) CD8+ T Cells from Kidney Transplant Recipients Exhibit Enhanced Purinergic P2X4 Receptor–Dependent Proinflammatory and Migratory Responses. Issue 12 (December 2022) - Doan Ngoc, Tra-My; Tilly, Gaëlle; Danger, Richard; Bonizec, Orianne; Masset, Christophe; Guérif, Pierrick; Bruneau, Sarah; Glemain, Alexandre; Harb, Jean; Cadoux, Marion; Vivet, Anaïs; Mai, Hoa Le; et al.
Significance Statement: The pathogenic role of terminally differentiated effector memory (TEMRA) CD8 + T cells has been implicated in kidney transplant failure. The authors showed that humoral rejection of kidney allografts is associated with an accumulation of cytolytic TEMRA CD8 + T cells in blood and in kidney graft biopsies. They demonstrated that TEMRA CD8 + T cells from kidney transplant recipients exhibit enhanced migratory properties compared with effector memory CD8 + T cells and that the chemokine CXCL12 not only promotes migration of TEMRA CD8 + T cells toward nonlymphoid organs but also triggers a purinergic P2X4 receptor–dependent proinflammatory response. They also found that agents aimed at potential TEMRA CD8 + T cell–specific targets inhibited the migration of TEMRA CD8 + T cells from kidney transplant recipients, suggesting a possible strategy in treating kidney transplant failure. Visual Abstract: Abstract : Background: The mechanisms regulating CD8 + T cell migration to nonlymphoid tissue during inflammation have not been fully elucidated, and the migratory properties of effector memory CD8 + T cells that re-express CD45RA (TEMRA CD8 + T cells) remain unclear, despite their roles in autoimmune diseases and allotransplant rejection. Methods: We used single-cell proteomic profiling and functional testing of CD8 + T cell subsets to characterize their effector functions and migratory properties in healthy volunteers and kidney transplant recipients with stable or humoral rejection. Results: We showed that humoral rejection of a kidney allograft is associated with an accumulation of cytolytic TEMRA CD8 + T cells in blood and kidney graft biopsies. TEMRA CD8 + T cells from kidney transplant recipients exhibited enhanced migratory properties compared with effector memory (EM) CD8 + T cells, with enhanced adhesion to activated endothelium and transmigration in response to the chemokine CXCL12. CXCL12 directly triggers a purinergic P2×4 receptor–dependent proinflammatory response of TEMRA CD8 + T cells from transplant recipients. The stimulation with IL-15 promotes the CXCL12-induced migration of TEMRA and EM CD8 + T cells and promotes the generation of functional PSGL1, which interacts with the cell adhesion molecule P-selectin and adhesion of these cells to activated endothelium. Although disruption of the interaction between functional PSGL1 and P-selectin prevents the adhesion and transmigration of both TEMRA and EM CD8 + T cells, targeting VLA-4 or LFA-1 (integrins involved in T cell migration) specifically inhibited the migration of TEMRA CD8 + T cells from kidney transplant recipients. Conclusions: Our findings highlight the active role of TEMRA CD8 + T cells in humoral transplant rejection and suggest that kidney transplant recipients may benefit from therapeutics targeting these cells.